2016
DOI: 10.3390/pathogens5030048
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Studies of Different Sequence Types and Geographical Origins of Streptococcus suis Serotype 2 in a Mouse Model of Infection

Abstract: Multilocus sequence typing previously identified three predominant sequence types (STs) of Streptococcus suis serotype 2: ST1 strains predominate in Eurasia while North American (NA) strains are generally ST25 and ST28. However, ST25/ST28 and ST1 strains have also been isolated in Asia and NA, respectively. Using a well-standardized mouse model of infection, the virulence of strains belonging to different STs and different geographical origins was evaluated. Results demonstrated that although a certain tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
107
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(116 citation statements)
references
References 60 publications
8
107
1
Order By: Relevance
“…However, important differences in virulence of isolates within this serotype have been described (Auger et al , 2016). It has been shown that Eurasian strains generally present a higher virulence potential than those from Canada and the USA, two countries that together are the second most important swine producers worldwide after China (Gottschalk, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, important differences in virulence of isolates within this serotype have been described (Auger et al , 2016). It has been shown that Eurasian strains generally present a higher virulence potential than those from Canada and the USA, two countries that together are the second most important swine producers worldwide after China (Gottschalk, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…are considered low virulent and have been mostly associated with secondary infections and immunocompromised individuals (8,9). Consequently, we chose ST1, ST7, and ST25 strains for our analyses because of their importance as predominant virulent S. suis serotype 2 strains, which are responsible for most porcine and human infections worldwide (3).…”
mentioning
confidence: 99%
“…As previously described, S. suis induced high plasmatic levels of the different proinflammatory mediators measured (interleukin-6 [IL-6], IL-12p70, interferon-␥ [IFN-␥], C-C motif chemokine ligand 3 [CCL3], CCL4, CCL5, C-X-C motif chemokine ligand 2 [CXCL2], and CXCL9) in wild-type mice (Fig. 2) (4,35). Levels of these mediators in the plasma of Nr4a1 Ϫ/Ϫ mice were similar to those of wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Though host death during the S. suis systemic infection is usually due to an exacerbated inflammatory response, a certain level of inflammation is required for bacterial elimination (10). As such, the role of monocytes in systemic inflammation was evaluated by measuring plasma mediators from wild-type, CCR2 Ϫ/Ϫ , and Nr4a1 Ϫ/Ϫ mice 12 h postinfection, corresponding to the time when production is maximal (4,35). As previously described, S. suis induced high plasmatic levels of the different proinflammatory mediators measured (interleukin-6 [IL-6], IL-12p70, interferon-␥ [IFN-␥], C-C motif chemokine ligand 3 [CCL3], CCL4, CCL5, C-X-C motif chemokine ligand 2 [CXCL2], and CXCL9) in wild-type mice (Fig.…”
Section: Resultsmentioning
confidence: 99%